Green and Blue Infrastructure and Nature-Based Solutions (NbS) in Metropolitan Areas: A Discussion for Resilient Cities - Affonso , Stella Bruna Ananias; Perez-Martinez, Pedro Jose (Technical and Scientific Journal Green Cities, 2025)
Objective – This article aims to present the concepts and research related to Green and Blue Infrastructure and Nature-Based Solutions (NbS) found in urban planning studies, focusing primarily on the pursuit of climate resilience in metropolitan regions. Methodology – To achieve the research objective, the methodology adopted consisted of a literature review based on previously published studies within the thematic axis, and the methodological approach employed was descriptive. Originality/Relevance – By exposing relevant aspects in the conceptualization and discussion of Green and Blue Infrastructure and NbS, focusing on metropolitan regions with large populations, this study proposes a way of thinking about these tools as strategies for building resilient cities, that is cities better adapted to climate change and with decisions that take into account the environment, as well as the health and well-being of their inhabitants. Results – Overall, the findings highlight that, after decades of urban growth without due environmental considerations, some of the damage is increasingly severe and some are already well-known today, such as rising temperatures and poor air quality, as well as floods and droughts. In this scenario, several authors point to the urgent need to adopt more sustainable measures in the management of urban centers and consider the inclusion of Green and Blue Infrastructure and NBS as possible options, as long as they are adapted to address local problems and complexities. Theoretical/Methodological Contributions – By synthesizing the definitions, as well as the applications and methods addressed in the studies, the research correlated the definitions and potential of Green and Blue Infrastructure and NBS to collaborate with other studies designed to formulate public policies aimed at building urban and mobility systems adapted to climate change. Social and Environmental Contributions – The research, by exploring these concepts within the context of climate resilience in urban centers, brings together authors as a way to update the discussion in search of spatial management focused on development based on a fairer relationship with the environment.